REPRESENTASI MAKNA SEMANTIK NILAI STOIKISME DALAM BUKU FILOSOFI TERAS KARYA HENRY MANAMPIRING - Putu Kania Arliani Tara; Made Sri Satyawati; I Gusti Ngurah Mayun Susandhika (CV. ADIBA AISHA AMIRA, 2026)
This study aims to identify and explain the representation of Stoic values in Henry Manampiring’s book “Filosofi Teras” through a semantic perspective. The issues examined include how Stoic values are represented in the text, the types of meaning used to represent these values, and the relationship between meaning and conceptual metaphors in shaping the reader’s understanding. This study employs a qualitative descriptive method with a semantic approach. The research data consist of words, phrases, sentences, and paragraphs in the book “Filosofi Teras” that contain Stoic values. Data collection was conducted using purposive sampling, while data analysis utilized the referential correspondence method. The results show that there are five core Stoic values represented in the book: the dichotomy of control, control of emotions and thoughts, rational perception, inner calm, and virtue and self-improvement. These values are represented through the use of lexical, denotative, and connotative meanings, as well as semantic relations. Furthermore, the use of conceptual metaphors and analogies plays a crucial role in simplifying philosophical concepts, making them easier for modern readers to understand.